Low-dose modified-release prednisone in axial spondyloarthritis: 3-month efficacy and tolerability - Bandinelli F; Scazzariello F; Pimenta da Fonseca E; Barreto Santiago M; Marcassa C; Nacci F; Matucci Cerinic M (Dove Medical Press, 2016)
Francesca Bandinelli,1 Francesco Scazzariello,1 Emanuela Pimenta da Fonseca,2 Mittermayer Barreto Santiago,2 Claudio Marcassa,3 Francesca Nacci,1 Marco Matucci Cerinic1 1Department of Experimental and Clinical Medicine, University of Florence, Florence, Italy; 2Service of Rheumatology, Hospital Santa Isabel, Escola de Medicina e Saúde Pública, Bahia, Brazil; 3Maugeri Clinical and Scientific Institutes, IRCCS, Veruno, Novara, Italy Background: Oral glucocorticoids (GCs) have been shown to be effective in reducing the inflammatory symptoms of rheumatoid arthritis, but their use is not supported by evidence in spondyloarthritis (SpA). Modified-release (MR) oral prednisone taken at bedtime has been shown to be more effective than immediate-release prednisone taken in the morning. The efficacy of low-dose MR prednisolone in patients with SpA is unknown. Patients and methods: This single-center cohort study retrospectively assessed the effectiveness and safety of 12-week low-dose MR prednisone (5 mg daily, bedtime administration) in GC-naïve adult patients with symptomatic axial SpA. A 50% improvement of the Bath Ankylosing Spondylitis Disease Activity Index (BASDAI) or a final BASDAI score of <4 according to disease activity at baseline was chosen as the primary outcome parameter after MR prednisone. Results: Fifty-seven patients were evaluated; of them, 41 had an active disease (BASDAI score of ≥4) at baseline. MR prednisone significantly reduced BASDAI (from 5.5±2.6 to 3.0±2.8, P<0.001) as well as inflammatory symptoms, pain, fatigue and morning stiffness. The overall response rate after MR prednisone was 52.6% (53.7% in patients with active SpA and 50.0% in patients with low-active disease; nonsignificant). At multivariable analysis, none of the considered clinical findings independently predicted the response to MR prednisone in subjects with active SpA. Overall, seven patients (11.8%) had nonserious adverse drug reactions after MR prednisone. Conclusion: In patients with symptomatic SpA and naïve to GCs, low-dose MR prednisone reduced the symptoms and clinical indexes of disease activity and showed a positive safety profile. Keywords: spondyloarthritis, morning stiffness, glucocorticoids, modified-release prednisone